2019
DOI: 10.3892/etm.2019.7978
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the severity of reflux esophagitis in children and changes in oxidative stress, serum inflammation, vasoactive intestinal peptide and motilin

Abstract: Changes in the levels of serum oxidative stress indexes, gastrointestinal hormones and inflammatory factors in children with different severity of reflux esophagitis (RE) were detected. Sixty child patients diagnosed with gastroesophageal reflux disease (GERD) via gastroscopy were selected and divided into non-erosive reflux disease group (NERD group, n=12) and RE group (n=48) according to whether there was esophageal mucosal injury. In RE group, the patients were further divided into grade I RE group (n=15), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…In this experiment, we confirmed the inhibitory effect of CLR on oxidative stress in ARE model. It is known that in ARE, ROS is produced in mucosal epithelial cells stimulated by reflux of gastric contents, which increases esophageal mucosal damage [ 42 ]. As a result of confirming the levels of ROS and ONOO − , biomarkers of oxidative stress in serum, it was significantly decreased in CM and CH, and TBARS levels, lipid peroxides in serum and tissue, were also significantly decreased in CM and CH (Figures 4 and 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, we confirmed the inhibitory effect of CLR on oxidative stress in ARE model. It is known that in ARE, ROS is produced in mucosal epithelial cells stimulated by reflux of gastric contents, which increases esophageal mucosal damage [ 42 ]. As a result of confirming the levels of ROS and ONOO − , biomarkers of oxidative stress in serum, it was significantly decreased in CM and CH, and TBARS levels, lipid peroxides in serum and tissue, were also significantly decreased in CM and CH (Figures 4 and 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al [6] investigated the association between the severity of reflux esophagitis (GERD group and ER group) in children and changes in OS, serum inflammation, vasoactive intestinal peptide (VIP), and motilin. The study concluded that patients with reflux esophagitis had OS (by measuring changes in MDA levels, total SOD, VIP, motilin, IL-1β, IL-8, and TNF) and elevated robust inflammatory response serum VIP (motility regulators), gastrointestinal tract, and decreased motilin levels.…”
Section: Relationship Between Tos Antioxidant Status and Osi With Gerd Degreementioning
confidence: 99%
“…High gastric acid stimulates oesophageal epithelial cells to create reactive oxygen species (ROS) and cause oxidative stress (OS) by activating macrophages, Proteinase-Activated Receptor 2 (PAR 2), and Platelet-Activating Factor [5]. The inflammatory process will be aided by OS, eventually resulting in mucosal damage [6].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive concentrations of free oxygen radicals in conditions of a lack of antioxidants such as reduced glutathione and SOD damage DNA and promote the development of esophageal adenocarcinoma [21]. There is a dependence of lipid peroxidation processes on the severity of GERD: the malonyldialdehyde content in the esophageal mucosa of patients with reflux esophagitis exceeded that in patients with non-erosive GERD, and the decrease in total SOD activity is inversely proportional to the severity of damage to the esophageal mucosa [22]. Oxidative stress accompanies thyroid diseases, while the mechanisms of its implementation depend on the functional state of the gland: in hyperthyroidism, the leading link is the overproduction of ROS, and in hypothyroidism, the low availability of antioxidants [23].…”
Section: Discussionmentioning
confidence: 99%